Racial/ethnic disparities in magnesium sulfate neuroprotection: a subgroup analysis of a multicenter randomized controlled trial. (2nd September 2018) - Vilchez, Gustavo; Dai, Jing; Kumar, Komal; Mundy, David; Kontopoulos, Eftichia; Sokol, Robert J.
Abstract: Objective: Despite known racial disparities in obstetrics, as well as differences in magnesium pharmacodynamics according to race, the effect of race/ethnicity in magnesium sulfate (MgSO4 ) use during pregnancy has not been studied. Whether some mothers are at increased risk of side effects, or infants at decreased neuroprotective effects is unknown. We analyze the effect of race/ethnicity in maternal/infant outcomes after MgSO4 neuroprotection. Study design: Subgroup analysis of a multicenter clinical trial (BEAM trial) where pregnant women at risk of preterm birth were randomized to either MgSO4 or placebo. For this study, nonanomalous singleton pregnancies were studied. The effect of race in maternal/neonatal outcomes after MgSO4 was analyzed with Breslow–Day and multifactorial ANOVA. Logistic regression was used to calculate odds ratios (OR) of complications according to race. Results: 922 MgSO4 and 972 placebo cases were included (45.0% African-American, 36.2% Caucasian, 17.8% Hispanics, and 1.0% Asians). Interaction analysis showed a significant effect of race/ethnicity ( p = .043). Hispanics presented the highest frequency (88.3%, p < .001), as well as the highest odds of MgSO4 side effects [OR(95%CI) = 6.6 (1.3–33.8)]. Conclusion: Hispanics present increased risk of magnesium toxicity compared to other racial/ethnic groups. Whether specific racial/ethnic groups require closer surveillance for early signs of magnesium toxicity needs to be further explored.